Maier, Sarah E., et al., editors. Neo-Victorian Things: Re-Imagining Nineteenth-Century Material Cultures in Literature and Film. Palgrave Macmillan, 2022. 233 pp. ISBN 978-3-031-06203-2 - Demirel, Özlem (FOCUS: Papers in English Literary and Cultural Studies, 2024)
In Neo-Victorian Things, editors Sarah E. Maier, Brenda Ayres, and Daniella Mariann Dove compile a comprehensive collection of essays, each of which discussing the role of material objects in neo-Victorian narratives. Dove and Maier centre upon the concept of thingness—a term they use to describe material objects in these narratives—suggesting that these objects do not merely represent the Victorian past but actively animate it, creating “a visceral, tactile and/or emotional” (2) experience for the modern reader. The volume’s theoretical framework is strongly grounded in Bill Brown’s Thing Theory,1which frames things as agents that actively shape the relationship between humans and things. This perspective in literary criticism is further enriched by newer approaches in object-oriented ontology, new materialism, phenomenology, and sensory studies. The Introduction lays out a well-rounded structure for the volume, unpacking the key terms of materialism and neo-Victorianism. It then offers an overview of how each chapter explores the complex relationship between things and humans across various neo-Victorian adaptations—be it literature or film. In chapter 2, Rosario Arias focuses on Deborah Lutz’s The Brontë Cabinet: Three Lives in Nine Objects (2015). Arias argues that Lutz’s approach to Victorian materiality is about more than mere historical curiosity; instead, it positions artefacts (such as Charlotte Brontë’s fern book) as dynamic entities that allow contemporary readers to form a sensory and emotional connection with the past. Arias’ analysis of Lutz’s work significantly contributes to neo-Victorianism in terms of reconstructing the daily lives of the Brontës. As Arias also highlights, Lutz’s study provides a deeply phenomenological reading of Brontës’ material world, focusing on the affective relationship between “objects and humans” (35).